Potential Sectors That Can Help Increase Local Revenue in Mahakam Ulu - Muhammad Harits Zidni Khatib Ramadhani; Muhammad Rinaldi; Abdurrahman Maulana Yusuf; Sitti Rahma Sudirman; Melda Aulia Ramadhani (Eastasouth Institute, 2023)
This study aims to find sectors that can contribute to the increase in Local Original Income (PAD) of Mahakam Ulu Regency. Mahakam Ulu Regency has the potential of natural and human resources that can be utilized to encourage regional economic growth. Therefore, this study was conducted to understand the sectors contributing to PAD. The research method used involves analyzing the economic data of Mahakam Ulu Regency, identifying potential resources, and mapping the sectors' potential using tools such as LQ analysis, Klassen typology analysis, and Shift Share analysis. The results showed that several potential sectors affect the increase in PAD in Mahakam Ulu Regency: agriculture, forestry, fisheries, warehousing, and transportation. To improve PAD, it is necessary to carry out a development plan that includes development strategies for potential sectors, supporting policies, and implementation steps.